Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1126/science.1080653
|View full text |Cite
|
Sign up to set email alerts
|

Magma Ascent and the Pressurization of Mount Etna's Volcanic System

Abstract: After a period of deflation during the 1991-1993 flank eruption, Mount Etna underwent a rapid inflation. Seismicity and ground deformation show that since 1994, a huge volume of magma intruded beneath the volcano, producing from 1998 onward a series of eruptions at the summit and on the flank of the volcano. The last of these, started on 27 October 2002, is still in progress and can be considered one of the most explosive eruptions of the volcano in recent times. Here we show how geodetic data and seismic defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(195 citation statements)
references
References 18 publications
13
180
1
1
Order By: Relevance
“…The velocity of this phenomenon appears near constant over the last two years in the western flank and also the deformation rate in this sector of the volcano is very similar to that observed during previous recent inflation periods. Accordingly with studies performed on the ground deformation measured on Mount Etna during the last years, the inflation observed on the western flank is the effect of the ''deep'' magma ascent (about 2 -5 km bsl), most probably along the western boundary of the high seismic velocity body revealed by the integration of recent seismic tomography and the ground deformation pattern [Patanè et al, 2003].…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…The velocity of this phenomenon appears near constant over the last two years in the western flank and also the deformation rate in this sector of the volcano is very similar to that observed during previous recent inflation periods. Accordingly with studies performed on the ground deformation measured on Mount Etna during the last years, the inflation observed on the western flank is the effect of the ''deep'' magma ascent (about 2 -5 km bsl), most probably along the western boundary of the high seismic velocity body revealed by the integration of recent seismic tomography and the ground deformation pattern [Patanè et al, 2003].…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…Etna mainly on the basis of ground deformation (Bonaccorso et al 1994;Bonaccorso 1996) and seismic data (Murru et al 1999;Patanè et al 2003). In particular, Murru et al (1999) found evidence of at least two magma reservoirs.…”
Section: Shallow Magma Reservoirsmentioning
confidence: 99%
“…Etna's plumbing system where complex mechanisms of crystal-melt separation took place. The cognate xenoliths are fragments of the intrusive rocks that were transported to the surface by the volatile-rich and fastascending, deep dyke-fed (DDF) eruptions of 1763 ("La Montagnola"), 2001, and 2002-03. Since seismological data (Patané et al 2003;Cocina, unpublished data) show that the HVB is aseismic, it's reasonable to think that the solidified intrusive rocks are not actively involved in magma dynamics and represent a peripheral zone of the present-day plumbing system.…”
Section: Discussionmentioning
confidence: 99%
“…The time-integrated spatial distribution of the seismicity revealed that the HVB is mainly aseismic. The seismicity encompasses its western and eastern portions, and occasionally is located above its top, testifying to the presence of a brittle region with a high degree of rock-fracturing (Aloisi et al 2002;Patané et al 2003;Chiarabba et al 2004). Recent studies have shed light on the possible role of the HVB in driving the instability phenomena of the eastern portion of the volcano Aloisi et al 2011).…”
Section: Introductionmentioning
confidence: 99%